Colibacillosis in breeding hens (Revista Sistemas de Producción Agroecológicos, 2018)
The colibacillosis in breeding hens is given by Gram negative bacteria, avian pathogenic enterobacteria Escherichia coli (APEC), which presents a high percentage of polymorphisms and plasticity in its genes, research reports common macroscopic findings: salpingitis, peritonitis and polyserositis, which entails at the death of the bird, three routes of contamination are defined, ascending through the cloaca of the bird, entry by respiratory way or bacterial translocation from the intestine; the diagnosis of colibacillosis is made from the history of the chicken coop, making necropsies and taking samples from swabs or tissue from organs such as oviduct, lung, heart or others affected organs are carried to means such as McConkey, eosin-methylene blue or drigalki agar for their isolation, as specific tests to Esceherichia coli are known methods based in phenotypes such as serotyping of immunological O/H, bacteriophage typing, electrophoresis with multilocus enzymes, Matrix-Assisted Laser Desorption/Ionization (MALDI-TOF) and methods based on genotypes such as restriction length polymorphism (RFLP), liminex-based suspension assay, amplified fragment length polymorphism (AFLP) and optical mapping. The vaccines for this bacterium have not been developed to perfection because it presents an immune response to its homologous, but no resistance to challenges with heterologous, is still researching the development of vaccines that may present a response to several serotypes of the bacteria, for now the effective way to control the bacteria is from of biosafety and prevention protocols to maintain the health of the animal.
Keywords: Escherichia coli; salpingitis; peritonitis; diarrhea; prevention